Li–Si thin films for battery applications produced by ion-beam co-sputtering. Issue 10 (6th February 2015) - Strauß, Florian; Hüger, Erwin; Heitjans, Paul; Trouillet, Vanessa; Bruns, Michael; Schmidt, Harald
<x xml:space="preserve">Abstract</x> Amorphous LixSi (x = 0.4) thin films were produced by reactive ion-beam co-sputtering for use as anode materials in Li-ion batteries.